Transforming Urban Space: The Success of Sustainable Regeneration in Speirs Locks - Medina Suci Handayani (West Science Interdisciplinary Studies, 2024)
This paper examines the Speirs Locks area regeneration project in Glasgow, focusing on the implementation of a sustainable and inclusive master plan aimed at revitalising the canal area. The study explores the strategic integration of urban planning principles, stakeholder engagement and environmental sustainability in the redevelopment process. Through qualitative analysis and case study methods, the research highlights the project's successes and challenges, particularly in improving the social, economic, and environmental conditions in the area. The findings show that despite facing physical and infrastructural constraints, the regeneration project has significantly improved the quality of life of the local community and set an example for future urban redevelopment initiatives.